Bird names as critical communication infrastructure in the contexts of history, language, and culture - Winker, Kevin (Zootaxa, 2024)
Standardized taxonomies and lists of birds were created to improve communication. They are linguistic infrastructure―biodiversity indices and dictionaries―that have been painstakingly built and maintained and that have enhanced regional and global participation in the study and enjoyment of birds. Inclusion of people has been a core objective in creating and maintaining these standardized lists, and dissatisfaction and desires to overwrite objectionable names have been associated with them for nearly two centuries. Suggestions that bird names should be changed are continuous. Today, these suggestions include the view that some bird names must be changed to make them more accurate, inoffensive, and culturally appropriate to further increase diversity and inclusion among ornithologists and bird watchers. The latter, meritorious goal has been largely successful thus far despite many ongoing objections. Historic examples indicate that large-scale name changes, however, are not needed to accomplish major societal goals of inclusion. Some barriers to inclusion likely remain, and some changes are likely needed for English names. Often overlooked or underappreciated in name change discussions are that: 1) standardized names lists have had numerically staggering success in fostering inclusion of diverse participants globally; 2) stability is vital in such systems, and destabilization has exclusionary effects; 3) dissatisfaction with such lists and the names they include has been ongoing since these naming systems began; 4) important flexibilities exist in conjunction with these communication systems that enhance local and regional communication (e.g., alternative names in English and other languages); and 5) cultural values, important as they are, are neither universally shared nor constant, and thus risk bringing divisiveness and instability when used as a central reason for change. Consideration of standardized lists of bird names as communication systems in the fuller context of history, language, and culture will improve our management of these systems and their continued utility in fostering inclusion. With standardized, stable naming systems acting as a skeleton, proactively building outwards, both within and among languages and cultures, offers a positive and productive way to increase inclusion and to improve cultural and biodiversity conservation.